Soilsurface temperatures in 2 cm depth between summer 2018 and 2019 with iButton-sensor 185 in the North Slope of Alaska, USA - Moritz Langer; Soraya Kaiser; Simone Maria Stuenzi; Thomas Schneider von Deimling; Alexander Oehme; Stephan Jacobi (PANGAEA, 2020)
Soil surface temperatures were collected with help of iButtons along different transects and clusters in the North Slope of Alaska. The interval was set to 4 hours resp. 4.25 hours. Different models of iButtons were used (with a resolution of 0.0625 °C and 0.5°C resp.), see Comment.
In: Langer, M et al. (2020): Soilsurface temperatures in 2 cm depth between summer 2018 and 2019 with iButton-sensors in the North Slope of Alaska (USA), around Churchill (Canada) and the region of Illirney and Lena-Viluy (Russia) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.914327